Basic Concepts of Intellectual Property Rights and Patent Laws in India: An Examination of Intellectual Property Rights and Patent Laws in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Mark Getty said that Intellectual property is the oil of the 21 century. Look at the richest men a hundred years ago they all made their money extracting natural resources or moving them around. All today's richest men have made their money out of intellectual property. And if it proved once that something so valuable then in that case it is duty of all to protect and preserve it. In order to protect and preserve this asset we always look upon the legal fraternity. The legal initiatives were taken to preserve such rights and it has been declared that Intellectual Property Rights are those statutory rights which allow the creator or inventor of the product to prevent others from exploiting the same commercially for a certain period of time. Intellectual Property includes Patents, Copyright, Designs and Trademarks etc. The vital role in protecting Intellectual Property Rights can be done the Judiciary only. Patent relates to new, useful and non-obvious processes, machines, manufactures, composition of matter, plants, or design. Another form of technology, which is more frequent, is the undisclosed proprietary information (know how) which is superior to the ordinary level of information in the industry concerned. In this research paper the researcher tried to highlight the importance of protecting Intellectual Property Rights and to promote Patent Laws for the promotion of good researches and inventions.